2006
DOI: 10.1002/asi.20350
|View full text |Cite
|
Sign up to set email alerts
|

Written versus spoken queries: A qualitative and quantitative comparative analysis

Abstract: This paper reports on an experimental study on the differences between spoken and written queries. A set of written and spontaneous spoken queries are generated by users from written topics. These two sets of queries are compared in qualitative terms and in terms of their retrieval effectiveness. Written and spoken queries are compared in terms of length, duration, and part of speech. In addition, assuming perfect transcription of the spoken queries, written and spoken queries are compared in terms of their ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…The initial formulation of a query strongly affects search results, and thus affects experimental results. Crestani and Du (2006) found that using speech to formulate one's information need provides a way to express it more naturally than for written topics. We believe that using spoken topics prevents users from copying keywords directly from given topics to formulate their queries.…”
Section: Search Topicsmentioning
confidence: 98%
“…The initial formulation of a query strongly affects search results, and thus affects experimental results. Crestani and Du (2006) found that using speech to formulate one's information need provides a way to express it more naturally than for written topics. We believe that using spoken topics prevents users from copying keywords directly from given topics to formulate their queries.…”
Section: Search Topicsmentioning
confidence: 98%
“…[163] Example 3: What are the differences between written and spoken queries in terms of their retrieval characteristics and performance outcomes? [62] Example 4: What is the relationship between query box size and query length? What is the relationship between query length and performance?…”
Section: Problems and Questionsmentioning
confidence: 99%
“…Schalkwyk et al [19] reported statistics of queries from Google Voice's search logs which found that voice queries are statistically shorter than desktop search queries. Crestani et al [6] conducted a user experiment based on collections of users' voice queries. However, the experiment environment did not involve a real search system.…”
Section: Related Work 21 Voice Searchmentioning
confidence: 99%
“…During voice search, users can vocalize their queries and the retrieval system utilizes the voice recognition results for retrieval [6,19]. Though previous studies found that query reformulation plays an important role in conventional textual search systems, to the best of our knowledge, there are very limited studies on voice search, especially concerning users' query reformulation in voice search.…”
Section: Introductionmentioning
confidence: 99%